RETRACTED: Sustainable development of enterprises as a priority for socio-economic transformations in the region - Medvedeva Lyudmila; Zemlyakova Nataliya; Averina Anastasia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001